2009
DOI: 10.1186/1756-3305-2-26
|View full text |Cite
|
Sign up to set email alerts
|

Role of the domestic dog as a reservoir host of Leishmania donovani in eastern Sudan

Abstract: Background: The study aims to determine the role of domestic dogs in transmission of visceral leishmaniasis in eastern Sudan. A cross-sectional survey was conducted in 10 villages along the River Rahad in eastern Sudan to elucidate the role of domestic dogs (Canis familiaris, Linnaeus, 1758) as a reservoir host of Leishmania donovani. In this study, 87 dogs were screened for infection by Leishmania donovani. Blood and lymph node samples were taken from 87 and 33 dogs respectively and subsequently screened by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
55
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 32 publications
5
55
5
Order By: Relevance
“…Leishmania DNA was detected in one sample taken from a stray dog in Fulbaria upazila using ITS1-PCR approach, as described previously [18], and sequencing analysis of the rRNA-ITS region and cytochrome b gene confirmed that this stray dog was infected with the L. donovani parasite. The presence of L. donovani DNA in the blood sample from a stray dog in our study supports the findings of a previous study in Sri Lanka [16], Sudan [11], and India [19]. In a more recent study in Nepal, Leishmania DNA was found in several domestic animals such as goats, cows and buffaloes from an endemic area several months after the active transmission season [4], but there was no evidence of Leishmania DNA in domestic cattle in Bangladesh, although the cattle were seropositive for leishmaniasis [1].…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Leishmania DNA was detected in one sample taken from a stray dog in Fulbaria upazila using ITS1-PCR approach, as described previously [18], and sequencing analysis of the rRNA-ITS region and cytochrome b gene confirmed that this stray dog was infected with the L. donovani parasite. The presence of L. donovani DNA in the blood sample from a stray dog in our study supports the findings of a previous study in Sri Lanka [16], Sudan [11], and India [19]. In a more recent study in Nepal, Leishmania DNA was found in several domestic animals such as goats, cows and buffaloes from an endemic area several months after the active transmission season [4], but there was no evidence of Leishmania DNA in domestic cattle in Bangladesh, although the cattle were seropositive for leishmaniasis [1].…”
supporting
confidence: 82%
“…In Asia and other parts of the world, dogs are the primary reservoir hosts of L. infantum, although canine infection is possible with L. donovani [8], the causative agent of human VL in the Indian subcontinent and East Africa. It has been documented in eastern Sudan that domestic dogs are an important reservoir host of L. donovani [11]. Results from our study suggest that dogs are a probable animal reservoir for L. donovani in this endemic focus.…”
supporting
confidence: 52%
“…It has been reported that the domestic dog may be an important reservoir host of L. donovani in eastern Sudan. 22 Some recent studies also reported reservoir hosts for Leishmania parasites other than dogs, such as red foxes in central Greece, 23 cats in the western provinces of Turkey, 24 and Brazilian bats. 25 In India, L. donovani DNA was recently detected in goats.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 In eastern Sudan, Phlebotomus orientalis and other sand flies are more attracted to dogs than to the mongoose, genet, and Nile rat. 22 Although there is a lack of information about the host preference of P. argentipes, the only known vector of L. donovani in Bangladesh, the feeding behavior of P. argentipes is mainly zoophilic 46 and animals act as the preferred blood meal source. 47 Hence, we recommend that further studies should examine the host preferences of P. argentipes to dogs and other animals in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…L. chagasi). Interestingly, some evidence has been presented that suggests that dogs also contribute to transmission in northeastern Africa, where L. donovani is the causative agent of human disease (17). Although the prevalence of Leishmania infection in dogs has been reported to rarely exceed 10%, it may rise up to 35% in areas where the disease is highly endemic (11).…”
mentioning
confidence: 99%